Pelatihan Keterampilan Konseling Sebaya dalam Bidang Kesehatan Reproduksi Remaja - Esty Aryani Safithry; Indah Sari Dewi; Fathul Zannah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
The great curiosity of adolescents to explore things is often not accompanied by careful consideration so that sometimes the actions are risky for themselves, others, and the surrounding environment. One problem that can arise is reproductive health problems. This training took place at the Muhammadiyah Health Vocational School in Palangkaraya and State High School 1 Palangka Raya with the reason that based on the results of interviews and questionnaires about knowledge of adolescent reproductive health which was still in the low category, no similar training had been carried out at the school. Students at the Vocational School are still teenagers too because they are engaged in health, which will go into the community and can then educate on Adolescent Reproductive Health. Peer groups can be used as a substitute for family, can function to stabilize the influence during the transition as a source of self-esteem, protection from adult coercion. Counselors who use peer counseling services can identify themselves with their peers, and the counselees assume that peer counselors have a willingness to build communication bridges. The results of this activity indicate that there is an increase in the average value of peer counseling skills in the field of adolescent reproductive health. The mean pre-test was 40.8, and the post-test mean was 67.4.